ChemInform Abstract: Fused Benzo[b]fluorenols: Palladium‐Catalyzed Intramolecular Dehydroaromatization and Carbonyl Reduction. Issue 10 (7th March 2013) - Zhao, Quansheng; Hu, Qiong; Wen, Lei; Wu, Min; Hu, Yimin
Abstract The target compounds are prepared under conditions A) in the presence of propargyl bromide as an optimal reactant.